A Two-step Protocol for Managing the Severe Consequences of Septic Arthritis in the Ankle - Chandan Narang; Girish Motwani; Rehan Ahmed (Journal of Foot and Ankle Surgery (Asia Pacific))
Aim: The aim of this study was to report a novel two-step technique for managing the severe consequences of septic ankle arthritis. Background: Septic ankle arthritis is a challenging orthopedic disease with a high risk of morbidity and mortality. Early treatment is essential to avoid irreparable articular cartilage damage and erosion, osteomyelitis, and dysfunctional painful foot and ankle deformities. Therefore, an aggressive surgical approach is essential to prevent severe extremity-threatening arthritis. Case description: We report that three of the cases of challenging septic ankle and ankle arthritis were treated with a two-phase protocol. The first stage included radical debridement, microbiological evaluation, insertion of vancomycin-coated biogranules, and administration of empirical intravenous antibiotics. In the second stage, deformity correction was performed by osteotomy and fixation. All three were asymptomatic at 6 months follow-up, had no discomfort in daily life and were able to perform fully functional activities. Conclusion: Two-stage protocol is a reliable way to manage septic arthritis of the ankle, with significant bone loss in the talar region and related deformities. It provides a good functional outcome of the limb with rigidness. It gives rigid, stable fixation using tibiotalocalcaneal nails.